(untitled) (Jurnal Geomine, 2022)
The study area is located in Sijunjung, and tectonically situated in Ombilin basin, which is considered as an intramountain basin or a sedimentary basin within a mountainous range of Bukit Barisan. Geological mapping has been previously carried out, and the present study conducts a structural evaluation by integrating field data and results of interpretation upon lineament using images of Digital Elevation Model (DEM), applying ArcGIS and PCI-Geomatic programs. Results of imagery analysis reveal that the lineament shows a general trend to NW-SE, and this orientation is consistent to that of structures developed in the region studied, especially those of Padangdoto, sesar Aie Angek, dan sesar Takung. The patterns of lineament and structure which are both directed to NW-SE can be interpreted that the region has been controlled by transtensional stresses due likely to the movement of active faults along the Bukit Barisan mountains.